Tourism and hotel development in China : from political to economic success - Zhang, Hanqin Qui; Pine, Ray ; Lam, Terry (New York, 2005)
Tourism and Hotel Development in China' is a comprehensive guide to the development of the tourism industry in mainland China following the end of the Cultural Revolution
Keywords: Tourism -- China Planning